First-principles study of bubble formation and cohesion properties of hydrogen at Fe/W interfaces. (8th October 2019) - Wang, Qian; Du, Guoping; Chen, Nan; Jiang, Changshuang
Abstract: First-principles study is used to comparatively investigate the mechanism of bubble formation of hydrogen at Fe/W interfaces and the effects of H on interface cohesion. It is found that hydrogen at interfacial sites has a negative binding energy, which is quite different from W and Fe bulks with interstitial hydrogen. The hydrogen solubility of the interface is bigger than W and Fe bulks with the increasing temperature, predicting that the Fe/W interface can more easily trap hydrogen and rapidly form bubbles. In addition, we also reveal the sites of hydrogen have an important role on cohesion properties of Fe/W interface, and that the obvious increase of interface strength and stability have been found in the locations of hydrogen relatively far away the center between Fe and W interface layers. The derived results are discussed extensively through comparing with available observations in the literature, and could give a deep understanding of hydrogen at Fe/W interfaces. Highlights: Hydrogen at Fe/W interface has a negative binding energy. The hydrogen solubility of Fe/W interface is bigger than W and Fe bulks with the increasing temperature. The location of hydrogen has an important role on cohesion properties of Fe/W interface. Our simulations agree well with similar experimental observations in the literature.